L.Kyianovs’ka’s Ideas in the Context of the New European Music Pedagogy Tendencies - Yuliya Poplavs’ka-Mel’nychenko (Pedagogical Discourse, 2013)
The article deals with our society’s attitude towards classical music, the reduction of the interest  to it. In this context the  effectiveness of modern Ukrainian music pedagogy has been outlined; the problems of the given methodological approaches to the  music lessons at general secondary  schools have been pointed out; imperfection of the ministerial programs on the given subject has been defined; certain articles of  L.Kyjanovska,  Doctor of Arts, professor, famous pedagogue and art critic have been worked out, on the basis of which  some music and pedagogical ideas as possible solutions to the outlined problems have been distinguished.